NUMERICAL INVESTIGATION ON BEHAVIOUR OF COLD-FORMED STEEL UNLIPPED CHANNEL SUBJECT TO COMBINED COMPRESSION AND BENDING - Budiman Budiman (University Muhammadiyah Jakarta, 2023)
Cold-formed steel has become an alternative construction material solution that has many advantages compared to other construction materials including hot-rolled steel. The need for a construction material that can be manufactured easily and has a large strength-to-dimension ratio has been able to be met by cold-formed steel. In this study, the cross-section of unlipped channel cold-formed steel is subjected to a combination of compression and bending loads. Numerical analysis was carried out to see the behavior and capacity of the cold-formed steel cross-section using the effective width approach using SNI 7971-2013 or AS/NZS 4600 and using numerical analysis using the finite element method with ABAQUS. A comparison of the results of the two approaches was conducted to see whether the codes were able to give accurate results in providing cross-sectional capacity values for cold-formed steel. Numerical analysis and section capacity estimation will be carried out based on existing research in the literature.